11-Oxygenated C19 steroids are the predominant androgens responsible for hyperandrogenemia in Cushing's disease. Issue 5 (29th September 2022) - Nowotny, Hanna F; Braun, Leah; Vogel, Frederick; Bidlingmaier, Martin; Reincke, Martin; Tschaidse, Lea; Auer, Matthias K; Lottspeich, Christian; Wudy, Stefan A; Hartmann, Michaela F; Hawley, James; Adaway, Joanne E; et al.
Abstract: Background: Symptoms of hyperandrogenism are common in patients with Cushing's disease (CD), yet they are not sufficiently explained by androgen concentrations. In this study, we analyzed the contribution of 11-oxygenated C19 steroids (11oxC19) to hyperandrogenemia in female patients with CD. Methods: We assessed saliva day profiles in females with CD pre ( n = 23) and post ( n = 13) successful transsphenoidal surgery, 26 female controls, 5 females with CD treated with metyrapone and 5 treated with osilodrostat for cortisol, cortisone, androstenedione (A4), 11-hydroxyandrostenedione (11OHA4), testosterone (TS), 11-ketotestosterone (11KT), as well as metabolites of classic and 11-oxygenated androgens in 24-h urine. In addition, morning baseline levels of gonadotropins and estradiol, sex hormone-binding globulin, cortisol and dehydroepiandrosterone sulfate (DHEAS) in serum and adrenocorticotrophic hormone in plasma in patients and controls were investigated. Results: Treatment-naïve females with CD showed a significantly elevated area under the curve of 11OHA4 and 11KT in saliva throughout the day compared to controls (11OHA4 mean rank difference (mrd) 18.13, P = 0.0002; 11KT mrd 17.42; P = 0.0005), whereas A4, TS and DHEAS were comparable to controls. Gonadotropin concentrations were normal in all patients with CD. After transsphenoidal surgery, 11oxC19 and their metabolites dropped significantly in saliva (11OHA4 P < 0.0001; 11KT P = 0.0010) and urine (11-oxo-androsterone P = 0.0011; 11-hydroxy-androsterone P < 0.0001), treatment with osilodrostat and metyrapone efficaciously blocked 11oxC19 synthesis. Conclusion: Hyperandrogenemia in CD is predominantly caused by excess of 11oxC19 steroids.